ANALISIS PERFORMA TOROIDAL PROPELLER - Bima Anugerah Putra (2024)
The toroidal propeller is a type of propeller that has a circular shape on its blades. This propeller is currently a topic of discussion because it is claimed to provide higher efficiency, lower noise levels, and several other advantages compared to the current propeller models. However, scientific publications on toroidal propeller research are still limited, and most rely only on field experiments. This study aims to compare the performance of the toroidal propeller with a conventional propeller of similar shape, to determine the extent of the improvement that can be produced by the toroidal propeller. The geometric parameters used to model the conventional propeller to resemble the toroidal include propeller diameter, number of leaves, hub diameter, and blade front view. The pitch geometric parameter on the conventional propeller is varied to determine whether the conventional propeller is able to produce efficiency similar to the toroidal propeller. Each propeller model in this study is simulated at 1000 - 6000 RPM using Computational Fluid Dynamics (CFD) simulation with Simscale software. This CFD simulation will produce thrust and torque values which are then calculated to obtain efficiency values. The results of the study show that the thrust and torque values on the propeller will increase along with the increase in pitch and RPM. In terms of efficiency, a variation of the conventional propeller with a pitch of 171.45 mm is able to produce higher efficiency values compared to the toroidal propeller, but has low thrust. This study also produces a visualization of fluid flow on each propeller model. The results show that the best fluid flow is owned by the toroidal propeller without any vorticity. Thus, this study can provide an understanding of the toroidal propeller and contribute to the further development of this technology design.